Individual and combined effects of arbuscular mycorrhizal fungi and phytohormones on the growth and physiobiochemical characteristics of tea cutting seedlings - GAO, Xiubing; LIU, Yan; LIU, Chunyan; GUO, Can; ZHANG, Yuan; MA, Chiyu; DUAN, Xueyi (Frontiers in Plant Science, 2023)
Both arbuscular mycorrhizal fungi (AMF) and phytohormones collectively regulate plant growth and root development, but their individual and combined effects on tea [Camellia sinensis (L.) O. Kuntze] cutting seedings remain unclear. This study examined the individual and combined effects of two species of AMF (Rhizophagus intraradices, RI and Funneliformis mosseae, FM) and two types of hormones (strigolactones, SLs; polyamines, PAs) on tea cutting seedings, by evaluating the growth and physiobiochemical characteristics of plants treated with the AMFs and/or hormones. The results showed that inoculation with either AMF individually significantly enhanced mycorrhizal colonization, plant growth, root morphological traits, photosynthesis, and antioxidant enzyme activity. Similarly, SL treatment alone improved AMF colonization, plant growth, chlorophyll content, and superoxide dismutase (SOD) activity, while PA application alone improved root-related triats, dehydrogenase activity (DHA), and chlorophyll content. Interestingly, the addition of a combination of AMFs and hormones significantly improved the growth and physiobiochemical characteristics of tea cutting seedings. SL and RI exhibited the most improvements to the colonization rate, plant growth, root-morphological traits, root DHA activity, photosynthesis, chlorophyll content, soluble sugar content in leaves, and the activities of antioxidant enzymes (SOD, POD, and CAT), compared to other treatment combinations (SL + FM, PA + RI, and PA + FM). Correlation analyses revealed a significantly (p < 0.05) positive correlation of root AMF colonization with root-related traits (e.g., DHA, root total length, surface area, and volume) and leaf-related traits (e.g., leaf area, shoot biomass, total chlorophyll, and antioxidant enzyme activities). This study demonstrated that while the apllication of individual AMF or phytohormone had a good effects on most growth and physiobiochemical characteristics parameters of tea cutting seedings, the additive effect was from specific combined of AMF and phytohormone. These results highlight the possibility for combined of AMF and phytohormone to improve the asexual reproduction of tea plants via cuttings.